Vascular Trauma of the Lower Pelvic Limb Revascularization or Amputation? - Moreno, Julio César Barajas; Sánchez, Morelos Adolfo García; Valdés, Karen Stefany Cortés; Larios, Zuri Sadai Grez; Longines, Fabian Cazares; Castillo, Diego Alberto Basurto (British Journal of Healthcare and Medical Research, 2024)
Introduction: Vascular trauma is a surgical emergency that has become a public health problem in the world and in Mexico for decades, due to an increase in violence, the inability to generate security and impunity on the part of the government. Objective: To describe the experience of the Surgery service of the surgical treatment of vascular trauma of the lower limbs. Material and method: This is a retrospective, longitudinal, observational and descriptive study of all patients surgically treated for emergency vascular trauma in the Surgery service of the "Balbuena" General Hospital of the Ministry of Health of Mexico City from January 2021 to January 2024. Results: 27 cases, all male with an average age of 28 years. Of the total number of records, 15 patients (56.6%) underwent vessel ligation, while 10 (37%) underwent vessel-vessel anastomosis. One primary amputation and seven additional amputations. Discussion: Obvious signs of vascular injury included bleeding or throbbing or expanding hematoma, murmur, thrill, etc. It is concluded that imaging helps in the diagnosis and planning of therapeutic intervention. Ultrasound is diagnostic and angiography by computed tomography in vascular mapping, or for intervention or punctuation in the 1st instance. Conclusions: vascular trauma of the lower limbs in Mexico is very frequent and becomes a challenge in decision-making, in the actions that have an impact on the rescue of the limb and the life of the patient, despite having a null hospital infrastructure installed.